2016
DOI: 10.1111/anu.12421
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid digestibility in gilthead sea bream fed diets containing native, re-esterified or acid vegetable oils

Abstract: Re‐esterified vegetable oils are obtained from a chemical esterification reaction between vegetable acid oils and glycerol. Due to their properties, it is expected that they have a higher nutritive value than their corresponding acid oils and a better digestibility than their native counterparts. The aim of this study was to determine the effect of re‐esterified oils with a different monoacylglycerol (MAG) and diacylglycerol (DAG) content, produced from palm or rapeseed, on fatty acid digestibility in gilthead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Nonetheless, the endogenous production of 16:0 and 18:0 might have increased in fish fed MFd, leading to a decreased apparent digestibility of those FA, as previously suggested in pigs Jørgensen and Fernández (2000) and in broiler chickens by Smink et al (2008). The observed ADC values of SFA in the fish oil diet (91%) are lower than those previously reported for European seabass (95%) at 20°C (Eroldoğan et al, 2013), but higher than values obtained for gilthead seabream (Sparus aurata; 83%) at 22°C (Trullàs, Fontanillas, Tres, & Sala, 2016) or for Atlantic halibut (83%) at 12°C (Martins et al, 2009). In salmonids, ADC values of SFA ranged from 47% to 86%, depending on the water temperature (1-12°C; Caballero et al (2002); Menoyo, Lopez-Bote, Bautista, and Obach (2003)).…”
Section: Discussioncontrasting
confidence: 74%
“…Nonetheless, the endogenous production of 16:0 and 18:0 might have increased in fish fed MFd, leading to a decreased apparent digestibility of those FA, as previously suggested in pigs Jørgensen and Fernández (2000) and in broiler chickens by Smink et al (2008). The observed ADC values of SFA in the fish oil diet (91%) are lower than those previously reported for European seabass (95%) at 20°C (Eroldoğan et al, 2013), but higher than values obtained for gilthead seabream (Sparus aurata; 83%) at 22°C (Trullàs, Fontanillas, Tres, & Sala, 2016) or for Atlantic halibut (83%) at 12°C (Martins et al, 2009). In salmonids, ADC values of SFA ranged from 47% to 86%, depending on the water temperature (1-12°C; Caballero et al (2002); Menoyo, Lopez-Bote, Bautista, and Obach (2003)).…”
Section: Discussioncontrasting
confidence: 74%
“…In the present study, the level of replacement of FO was formulated according to previous studies in rainbow trout and gilthead seabream [12,15,16,29] and to ensure the reported requirements of n − 3 HUFA for European seabass in older juvenile and pre-adult stages [19,30,31]. This level of replacement of FO (75%) with crude vegetable oils (soybean and olive pomace oils) did not affect the performance, achieving similar final weights and FCR.…”
Section: Performance and Carcass Parametersmentioning
confidence: 99%
“…In fact, soybean-sunflower acid oil is the most widely available in the European market. Information about the effects of oils rich in FFA on farmed fish species is scarce, and only a few studies using palm fatty acid distillate (90% of FFA) or rapeseed acid oil (47% of FFA) in rainbow trout (Oncorhynchus mykiss) [12][13][14][15] and gilthead seabream (Sparus aurata) [16] have been found in the literature.…”
Section: Introductionmentioning
confidence: 99%